2004
DOI: 10.1098/rstb.2003.1393
|View full text |Cite
|
Sign up to set email alerts
|

Several million years of stability among insect species because of, or in spite of, Ice Age climatic instability?

Abstract: There is a curious paradox in the evolutionary legacy of Ice Ages. Studies of modern species suggest that they are currently evolving in response to changing environments. If extrapolated into the context of Quaternary Ice Ages, this evidence would suggest that the frequent climatic changes should have stimulated the evolutionary process and thus increased the rates of change within species and the number of speciation events. Extinction rates would, similarly, be high. Quaternary insect studies call into ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 16 publications
2
82
0
Order By: Relevance
“…The paleontological record also shows that communities of species did not move en masse and intact. Rather, communities were being continually disassembled and reassembled into new constellations of species (Coope 1995(Coope , 2004Graham et al 1996). As a result, new sets of interacting species may have been continually thrown together, and those species would have had to adjust evolutionarily to the new selection pressures these interactions engendered.…”
Section: Discussionmentioning
confidence: 99%
“…The paleontological record also shows that communities of species did not move en masse and intact. Rather, communities were being continually disassembled and reassembled into new constellations of species (Coope 1995(Coope , 2004Graham et al 1996). As a result, new sets of interacting species may have been continually thrown together, and those species would have had to adjust evolutionarily to the new selection pressures these interactions engendered.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic oscillations of the Pleistocene do not appear to have stimulated the same turnover of Australian biodiversity compared with earlier epochs, possibly because the continent already contained biota that were adapted to the alternating expansions and contractions of the arid and mesic zones. The ranges of ancestral mesic taxa expanded when the dry biomes contracted, and arid-adapted lineages would reclaim their range accordingly when the dry climate returned [38][39][40]. This provided biotic stability and a lack of open niches into which new species could radiate.…”
Section: (D) Diversification Of Wood-feeding and Soil-burrowing Lineagesmentioning
confidence: 99%
“…Therefore, instead of focusing on what promotes the speciation and radiation of Coleoptera, it might be more appropriate to focus on why beetles, polyphagans in particular, are less susceptible to extinction. Work focused on the Quaternary and Late Neogene has demonstrated that beetles are quite resilient to extinction, owing to their ability to change their geographical distributions in response to climate change [59]. In fact, ecology, morphology and geographical range size [54,60,61] are thought to contribute to extinction risk and in fact, many of these traits may be phylogenetically constrained [62,63].…”
Section: Penn P Ep Mp P Mp M Lpet T E E E Et T P Pe T T Mt T T T T T mentioning
confidence: 99%